Extra-Regional Influence on the Development of Economic Integration in the ASEAN Region - A. M. Titovich; A. V. Toropygin (Евразийская интеграция: экономика, право, политика, 2023)
This study discusses the extra-regional influence and scenarios for the development of regional integration of the countries of the Association of States Southeast Asia (ASEAN), in particular, the role of the future free trade agreement between the EAEU and Indonesia in maintaining the effect of convergence in Southeast Asia (Southeast Asia) in the horizon of 2025.Aim. To Determine the main trends in the development of extra-regional influence and forecasts for regional economic convergence in ASEAN countries by 2025.Tasks. Determine the trends and perspective scenarios for the development of the integration of the countries of Southeast Asia.Methods. Both the descriptive method and the system analysis method are used. Also, this study uses the approaches of the Eurasian Development Bank to assess the disproportion in the level of development of the ASEAN countries (macroeconomic indicators; in the analysis of time series of GDP, GDP per capita for ASEAN countries, the Box-Jenkins methodology (ARIMA) is used. The key concept in this study is convergence. Convergence is seen as the process of approaching a certain level or decreasing the difference between two values over time [7]; real convergence contributes to the convergence of the economic level of countries within an integrated group (differences in the economic levels of development of countries hinder the process of integration). The effect of real economic convergence for ASEAN countries in the future 2025 can take on different meanings depending on the implementation of the initiatives proposed by non-regional actors (for example, Indo-Pacific Economic Structure and FTA between the EAEU and Indonesia).Results. The results of the study present four probability-ranked scenarios for the development of regional economic convergence in the ASEAN countries. It has been established that the most likely scenario is one in which the initiative of the EAEU and the Republic of Indonesia will take place, while the Indo-Pacific Economic Structure proposed by the United States will not be implemented by 2025. In this case, regional economic convergence in the ASEAN countries may take on the most favorable meaning.Conclusions. Along with the global trend, the expansion of economic integration through the creation of free trade zones with other integration associations, the development of economic integration in the region is influenced by the rivalry between the People’s Republic of China and the United States of America. Looking forward to the mid-second half of the 2020s. years as a result, the adoption of a free trade agreement between the EAEU countries and the Republic of Indonesia will have a positive impact on the increase in the pace of regional economic convergence in Southeast Asia.